2014
DOI: 10.1007/s00345-014-1452-9
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of the role of UroVysion FISH assay in surveillance of patients with bladder cancer: does FISH positivity anticipate recurrence?

Abstract: Patients with a positive FISH and atypical cytology are more likely to recur even in the absence of visible tumor. FISH positivity may portend a higher risk for progression. These findings require prospective validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 19 publications
0
38
0
3
Order By: Relevance
“…9,38 With the exception of a recently published small study of cases reclassified as "AUC" according to the Paris System criteria 67 that found that the sensitivity and specificity of U-FISH for predicting urothelial carcinoma were only 85.7% and respectively 33.3%, no previous study was designed to specifically address the value of U-FISH tests in patients with a diagnosis of AUC. 9,38 With the exception of a recently published small study of cases reclassified as "AUC" according to the Paris System criteria 67 that found that the sensitivity and specificity of U-FISH for predicting urothelial carcinoma were only 85.7% and respectively 33.3%, no previous study was designed to specifically address the value of U-FISH tests in patients with a diagnosis of AUC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,38 With the exception of a recently published small study of cases reclassified as "AUC" according to the Paris System criteria 67 that found that the sensitivity and specificity of U-FISH for predicting urothelial carcinoma were only 85.7% and respectively 33.3%, no previous study was designed to specifically address the value of U-FISH tests in patients with a diagnosis of AUC. 9,38 With the exception of a recently published small study of cases reclassified as "AUC" according to the Paris System criteria 67 that found that the sensitivity and specificity of U-FISH for predicting urothelial carcinoma were only 85.7% and respectively 33.3%, no previous study was designed to specifically address the value of U-FISH tests in patients with a diagnosis of AUC.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, since the U-FISH test positivity can precede ("anticipate") the UC diagnosis by 30 months 37 or even more 38 we used extended follow-up periods of 18 and 36 months to determine if there is any improvement of the U-FISH test performance with longer follow-up intervals. This follow-up period was selected to allow accrual of follow-up data on both high risk and low risk patients, and to account for "anticipatory" positive results, i.e., positive U-FISH tests that are initially considered falsepositive as they precede a diagnosis of UC, but which frequently become true positive within 12 months of the index U-FISH test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a positive cytology are usually taken to the operating room for a biopsy and selective upper tract cytology, but that is not the case for positive markers. The concept of anticipatory positives is based on the concern that a marker can detect disease before it is visualized, but it is still not clear if this is clinically useful information [15]. …”
Section: Urinary Biomarkers For the Surveillance Of Bladder Cancer Pamentioning
confidence: 99%
“…Seideman et al investigated the role of FISH in patients with previous BCa who presented at follow-up with both negative cytology and cystoscopy. In such cases, FISH was able to anticipate disease Rec at a median follow-up of 26 months; mean time to Rec was 12.6 months in patients who were FISH positive compared to 17.9 months in those with negative FISH ( p  = 0.03) [15]. …”
Section: Urinary Biomarkers For the Surveillance Of Bladder Cancer Pamentioning
confidence: 99%